Enriched Virtual Blended Learning Model Assisted by Digital Comics: Its Effect on Student Learning Motivation - Ryan Brilian Fatsena; Basori; Agus Efendi (Informatics Education Department, Faculty of Teacher Training and Education, Universitas Sebelas Maret, 2024)
The Enriched Virtual Blended Learning model, assisted by digital comics, has attracted attention in the world of education for its positive influence on student motivation. This model requires students to study material both before and after class sessions. An experimental research method was used to determine the effect of this learning model on student motivation, as defined by four key indicators: